Comparison of Single Port Access Versus Multiple Port Access Systems in Elective Laparoscopy: 98 Dogs (2005–2014). Issue 7 (10th September 2015) - Gonzalez‐Gasch, Esteban; Monnet, Eric
<x xml:space="preserve">Abstract</x> Objective To report and compare the duration of surgery, the frequency of complications, and the frequency of open conversion for elective surgeries performed with 2 laparoscopic techniques: a single incision port access system (SPAS) and a multiple port access system (MPAS) using a Veress needle. Study Design Retrospective case series. Animals Ninety‐eight consecutive, client owned dogs. Methods Medical records of dogs undergoing an elective laparoscopic procedure were reviewed. Dogs were classified as SPAS or MPAS according to the initial surgical approach. Duration of surgery, intraoperative complications, reason for open conversion, and postoperative complications were recorded and compared. Results The duration of surgery for SPAS gastropexy (P = .0039), ovariectomy (P = .0052), and gastropexy/ovariectomy combined (P = .0002) were significantly reduced compared to corresponding MPAS procedures. Nine splenic punctures occurred during MPAS. The frequency of intraoperative complications was significantly less for SPAS (0/44) than MPAS (12/54, P = .004). Elective conversion was performed because of gastric malpositioning in 1 dog and emergent conversion was required because of bleeding from the ovarian pedicle in 2 dogs (0/44 SPAS, 3/54 MPAS, P = .250). There were 14/76 dogs with followup to suture removal with postoperative complications, all incisional (7/31 SPAS, 7/45 MPAS, P = 1.0). Conclusion The use of SPAS for laparoscopy reduced surgical time and intraoperative complications in elective procedures.